Tropical glacier meltwater contribution to stream discharge: a case study in the Cordillera Blanca, Peru - Mark, Bryan G. (2003)
Original abstract: Discharge measurements, climate observations and hydrochemical samples gathered monthly (1998/99) in the Yanamarey and Uruashraju glacier-fed catchments of the Cordillera Blanca, Peru, permit an analysis of the glacier meltwater contribution to stream-flow. These glacier catchments feed the Río Santa, which discharges into the Pacific Ocean. Based on a water-balance computation, glacier melt contributes an estimated 35% of the average discharge from the catchments. For comparison, a volumetric end-member mixing model of oxygen isotopes shows glacier melt contributes 30–45% to the total annual discharge. Based on stream geochemistry, discharge from the Yanamarey glacier catchment provides 30% of the annual volume discharged from the Querococha watershed, which is <10% glacierized. By analogy, the larger Río Santa watershed, also <10% glacierized, receives at least 12% of its annual discharge from melting glacier ice. Tributary watersheds to the Río Santa with larger fractions of glacier cover have less variable runoff and enhanced discharge, demonstrating that the glaciers effectively buffer stream discharge seasonally. With continued glacier melting, stream-flow will likely become more variable, and there will be less dry-season runoff.